Adoption of E-Wallet Usefulness and E-Wallet Risk in Impulsive Buying: Testing the Moderating Role of Low Distribution Charges in Post Covid-19 Era - Ali, Sharafat; Khan, Rana Israr Ahmad; Nasir, Nadia; Ghaffar, Muniba (Pakistan Journal of Humanities and Social Sciences, 2023)
This study's goal is to evaluate the extent to which low distribution charges are contributing part in impulsive buying when the customers in Pakistan have prospect of digital money for environment sustainability. Since different microfinance, profitable banking institutions and online businesses are providing digital services to enhance environmental sustainability in Pakistan, online purchasing is being increased. Prominently, a response rate of 40% was anticipated from the 650 questionnaires that were given out to pertinent responders. The results show that low distribution charges should be taken into consideration by online brands and businesses operating in Pakistan to enhance production and growth in Pakistan's impulsive purchasing market share. Additionally, study provides theoretical foundation to corpus exploration on impulsive purchases. Additionally, it provides essential future directions that will be crucial for current research and successfully contribute.